Application of The SD-WAN Load Balancing Method in Managing Internet Bandwidth at IDN Bogor Vocational School - Iskandar, Dadang; Farisyihab, Joe Renaldy; Bahari, Muhamad Hasbi Toharudin; Nurfaishal, Muhammad Dzaky; Khairullah, Muhammad Daffa (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The rapid growth of SMK IDN since its establishment in 2016 has necessitated the addition of several branches. With the increasing number of branches, SMK IDN's administrative activities need to be centralized at SMK IDN Jonggol (Central), where the school leases and utilizes MPLS services to support interconnections between branches and the central office. However, there are considerations regarding using MPLS services as the number of SMK IDN branches continues to grow. Concerns from the SMK IDN IT team include issues related to the inflexibility of MPLS links, which can only be specifically used for interconnecting branches or private links that cannot simultaneously accommodate the internet needs of branches. In this situation, the SMK IDN IT team seeks an efficient solution that provides flexibility in interconnections from branches to the central office, with capabilities and stability equal to or better than before. In response to the challenges faced by SMK IDN, we propose the Load Balancing SDWAN solution, where SMK IDN only needs to use internet services available at the central office and branches. The Load Balancing SDWAN solution offers flexibility in terms of cost efficiency and link usage because links can simultaneously fulfill internet and interconnection needs for branches. In its implementation, the Load-balancing SDWAN method effectively addresses the challenges encountered by SMK IDN. Test results show that after implementing the Load Balancing SDWAN method, there is a significant improvement in internet access stability for users, with the ability to failover if there are issues with one internet link, as well as maintaining secure and private connections between the central office and branches. Another benefit of implementing the Load Balancing SDWAN method is budget efficiency, as SMK IDN can provide dedicated internet services per month at a 63% lower cost compared to renting MPLS links previously used